Conceptualizing, Measuring, and Theorizing Dynamic De/Centralization in Federations - Dardanelli, P.; Kincaid, J.; Fenna, Alan; Kaiser, A.; Lecours, A.; Singh, A. (OUP, 2019)
This article develops a conceptual, methodological, and theoretical framework for analyzing dynamic de/centralization in federations. It first reviews the literature and outlines the research design and methods adopted. It then conceptualizes static de/centralization and describes the seven-point coding scheme we employed to measure it across twenty-two policy areas and five fiscal categories at ten-year intervals since the establishment of a federation. The subsequent section conceptualizes dynamic de/centralization and discusses its five main properties: direction, magnitude, tempo, form, and instruments. Drawing from several strands of the literature, the article finally identifies seven categories of causal determinants of dynamic de/centralization, from which we derive hypotheses for assessment.